Including Students who Are Visually Impaired in the Classroom: Attitudes of Preservice Teachers. (March 2015) - Ajuwon, Paul M.; Sarraj, Huda; Griffin-Shirley, Nora; Lechtenberger, DeAnn; Zhou, Li
Introduction: This study examines the perceptions of preservice teachers concerning the inclusion of students with blindness or low vision (visual impairments) in their classrooms. Methods: Using a modified version of the Preservice Inclusion Scale (PSIS), data were collected from participants in three universities in the United States before and after the completion of an introductory special education course. A Multivariate Analysis of Variance (MANOVA) test was conducted to investigate the change in participants' attitudes toward inclusion. Results: The anxiety measure revealed an increase in the calmness level of preservice teachers, and the receptivity measure revealed a nonsignificant change in their receptivity level toward inclusion. Discussion: There were three main study outcomes: A between-subject effect of the universities was not evident, no significant changes in hostility or receptivity were found, and the confidence of preservice teachers in teaching students with visual impairments was not a predictor of changes in attitudes toward inclusion. Suggestions for future research: Future research should determine the nature and scope of strategies included in coursework, and whether these strategies relate more to improvements in attitudes than to coursework that does not include them.